The Finger of Fate: A Romance - Reid, Mayne, 1818-1883 (Salt Lake City, UT : Project Gutenberg, 2011)
"The Finger of Fate: A Romance" by Captain Mayne Reid is a novel written in the late 19th century. The story revolves around the lives of two half-brothers, Nigel and Henry Harding, who come from a well-to-do family stemming from their father, General Harding. The novel explores themes of familial conflict, rivalry, and love as both brothers find themselves enamored with the same woman, Belle Mainwaring, setting the stage for an engaging tale of romance intertwined with complex relationships. The opening of the book introduces us to the Harding brothers during a hunting trip, illustrating their contrasting personalities and backgrounds. Nigel, the elder brother with a stern demeanor, clashes with Henry, whose warm-hearted and impulsive nature is depicted during an altercation that leads to a promise of vengeance between them. The narrative further unfolds their family dynamics, revealing their shared father but different mothers, highlighting underlying tensions and differing traits inherited from their parents. As the story progresses, the brothers' rivalry intensifies due to their mutual affection for Belle, creating a compelling backdrop for the unfolding drama. (This is an automatically generated summary.)
Release date is 2011-04-19
Produced by Nick Hodson of London, England
Keywords: Fiction